Modified reinforced conductive adhesive as well as preparation method and application thereof
By combining modified sheet-like silver-clad copper powder and sputtered carbon-based auxiliary filler, the problems of insufficient conductivity and high curing threshold of conductive glue are solved, and high conductivity and thermal conductivity are achieved, which is suitable for microelectronic packaging materials.
Patent Information
- Application Number
- CN202411252412.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing conductive adhesives have problems such as insufficient conductivity, high curing threshold, high cost and small thermal conductivity in microelectronic packaging, making it difficult to replace traditional tin lead solder.
Using modified sheet-like silver-clad copper powder, sputtered carbon-based auxiliary filler and acetylacetone metal salt, the construction of the conductive network is enhanced through surface modification treatment and magnetron sputtering technology, reducing volume resistivity and improving thermal conductivity .
It significantly improves electrical and thermal conductivity, shortens curing time, reduces production costs, and enhances curing strength. It is suitable for semiconductor packaging materials.
Smart Images

Figure CN119119935A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive adhesives, and in particular relates to a modified and enhanced conductive adhesive and a preparation method and application thereof. Background Art
[0002] With the rapid development of microelectronic devices, electronic components are gradually shifting towards high integration. Traditional tin-lead solder can no longer meet the requirements of the modern microelectronics industry due to defects such as high pollution, high curing temperature, and large size. Therefore, the microelectronics packaging industry needs packaging materials with better performance that can replace tin-lead alloy solder.
[0003] Conductive adhesive has the high conductivity and adhesion properties of tin-lead solder, while avoiding the toxicity and pollution of tin-lead solder. It is a very promising material for microelectronic packaging technology.
[0004] Most conductive adhesives in the prior art use silver powder as a conductive filler, but pure silver particles are easily oxidized and prone to electromigration. At the same time, pure silver particles as a conductive filler will also increase the cost of epoxy conductive adhesives. In addition, most existing conductive adhesives use a simple epoxy anhydride matrix, which has a high curing threshold, a long curing time, a low degree of conductive network construction, a small thermal conductivity, and a low shear strength. Summary of the invention
[0005] The purpose of the embodiments of the present invention is to provide a modified and enhanced conductive adhesive, aiming to solve the problems raised in the above background technology.
[0006] The embodiment of the present invention is implemented as follows: a modified and enhanced conductive adhesive includes the following raw materials in weight percentage: 18-25% bisphenol A epoxy resin, 60-75% modified flaky silver-coated copper powder, 0.2-0.5% sputtered carbon-based auxiliary filler, 0.3-0.5% acetylacetone metal salt, 1.1-1.6% coupling agent, and the balance is made up of curing agent.
[0007] Preferably, the bisphenol A epoxy resin is bisphenol A epoxy resin E-51 or a mixture of bisphenol A epoxy resin E-51 and bisphenol A epoxy resin E-42, and the weight ratio of bisphenol A epoxy resin E-51 to bisphenol A epoxy resin E-42 in the mixture is 18-20:1-3.
[0008] Preferably, the coupling agent is one of silane coupling agents KH-550 and KH-570 or a mixture of the two, and the weight ratio of KH-550 to KH-570 is 17-19:1-2.
[0009] Preferably, the acetylacetonate metal salt is one or a mixture of cobalt (II) acetylacetonate, cobalt (III) acetylacetonate, and chromium acetylacetonate, and the weight ratio of cobalt (II) acetylacetonate, cobalt (III) acetylacetonate, and chromium acetylacetonate is 1:0.1-0.4:0.1-0.4.
[0010] Preferably, the curing agent is methylhexahydrophthalic anhydride or a mixture of methylhexahydrophthalic anhydride and methyltetrahydrophthalic anhydride, and the weight ratio of methylhexahydrophthalic anhydride to methyltetrahydrophthalic anhydride in the mixture is 17-19:1-3.
[0011] Preferably, the modified flaky silver-coated copper powder has a particle size of 5-10 μm and a thickness of 250-500 nm, and its preparation method comprises the following steps:
[0012] Dispersing flaky silver-coated copper powder in anhydrous ethanol to prepare flaky silver-coated copper slurry;
[0013] The modified flaky silver-coated copper powder is obtained by pouring the flaky silver-coated copper slurry into the modified solution, stirring, standing, centrifuging and drying. The modified solution is anhydrous ethanol or a mixed solution of anhydrous ethanol and ethylene glycol. The weight ratio of anhydrous ethanol to ethylene glycol in the mixed solution is 1-4:1-5.
[0014] Preferably, the method for preparing the sputtered carbon-based auxiliary filler comprises the following steps:
[0015] Dispersing the carbon material in an aqueous solution of a surfactant and performing ultrasonic dispersion;
[0016] After the ultrasonic dispersion is completed, the mixture is filtered and dried, and a metal target is magnetron sputtered on the surface to obtain the sputtered carbon-based auxiliary filler.
[0017] Preferably, the carbon material is one or a mixture of carbon black, carbon fiber, and carbon nanotubes, and the weight ratio of carbon black, carbon fiber, and carbon nanotubes is 1-3:1-2:1-3;
[0018] The surfactant is one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate or a mixture of the two;
[0019] The metal target material for sputtering is one or a mixture of silver target, copper target, and nickel target. The sputtering power of the silver target, copper target, and nickel target is 50-100W.
[0020] Another object of the embodiment of the present invention is to provide a method for preparing a modified and enhanced conductive adhesive, comprising the following steps:
[0021] The bisphenol A epoxy resin is heated at a constant temperature;
[0022] Grinding the acetylacetone metal salt, adding the acetylacetone metal salt to the bisphenol A type epoxy resin, and stirring thoroughly to obtain a matrix;
[0023] Adding a coupling agent and a curing agent into the matrix, performing ultrasonic treatment, and waiting for the stratification phenomenon to disappear, thereby obtaining a modified matrix;
[0024] The sputtered carbon-based auxiliary filler and the modified flaky silver-coated copper powder are fully shaken and mixed to obtain a mixed filler;
[0025] The mixed filler is added into the modified matrix in batches and slowly stirred to obtain the modified enhanced conductive adhesive.
[0026] Another object of the embodiments of the present invention is to provide an application of a modified and enhanced conductive adhesive in the preparation of semiconductor packaging materials.
[0027] A modified and enhanced conductive adhesive provided by an embodiment of the present invention is added with modified flaky silver-coated copper powder. The modified flaky silver-coated copper powder is a surface-modified flaky silver-coated copper powder. Generally, organic matter is attached to the surface of the flaky silver-coated copper powder. The modified solution can effectively remove these organic matter, increase the contact between the silver-coated copper powders, thereby greatly improving the conductivity, ensuring the optimal curing time, and further reducing the resistivity; the added acetylacetone metal salt is used as a curing accelerator, which is first dissolved in the epoxy resin to prepare the modified epoxy resin, and then gradually In the first step, a coupling agent and a curing agent are added to prepare a modified matrix. Acetylacetone metal salt does not change the rheological properties of the epoxy resin, but can greatly shorten the curing time, lower the curing threshold, and increase the construction strength of the conductive network, thereby greatly reducing the volume resistivity. The addition of the coupling agent can increase the connection between the epoxy resin and the silver-coated copper powder and enhance the curing strength. Sputtered carbon-based auxiliary fillers are added, and metal nanoparticles are sputtered on the surface of the carbon material through magnetron sputtering technology to enhance the construction of the conductive network, thereby greatly reducing the volume resistivity and improving the thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The average particle size results of carbon black, carbon nanotubes and carbon fibers dispersed in SDS solution;
[0029] Figure 2 XRD comparison diagram of carbon black, carbon nanotubes and carbon fibers before and after dispersion in SDS solution;
[0030] Figure 3 Electron micrographs of carbon black, carbon nanotubes and carbon fibers before and after dispersion by adding SDS solution (a is untreated carbon black, b is untreated carbon nanotubes, c is untreated carbon fibers, d is treated carbon black, e is treated carbon nanotubes, and f is treated carbon fibers);
[0031] Figure 4These are the SEM-EDS images of Ag target, Cu target and Ni target after sputtering on carbon black as the substrate (ad is the sputtered Ag target, be is the sputtered Cu target, and cf is the sputtered Ni target). DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0033] A modified and enhanced conductive adhesive, the preparation method of which comprises the following steps:
[0034] (1) placing the bisphenol A epoxy resin in a vacuum drying oven and heating it at a constant temperature of 60° C. to improve the rheological properties of the epoxy resin;
[0035] (2) grinding the acetylacetone metal salt to increase the fineness, then adding the acetylacetone metal salt to the bisphenol A epoxy resin and stirring thoroughly, heating the vacuum drying oven to 60-100° C., placing the substrate in the oven, and maintaining the vacuum temperature for 30-60 minutes;
[0036] (3) adding a coupling agent and a curing agent, stirring slowly, and ultrasonicating at 25-30° C. for 10-20 min until the stratification phenomenon disappears, thereby obtaining a modified matrix;
[0037] (4) fully shaking and mixing the sputtered carbon-based auxiliary filler and the modified flaky silver-coated copper powder to obtain a mixed filler;
[0038] (5) Adding the mixed filler into the modified matrix in batches and slowly stirring the mixture to obtain the modified enhanced conductive adhesive.
[0039] The method for preparing the sputtered carbon-based auxiliary filler comprises the following steps:
[0040] (1) dispersing the carbon material in an aqueous solution of sodium dodecyl sulfate and ultrasonically dispersing for 30-60 minutes;
[0041] (2) filtering and vacuum drying the solution after the ultrasonic treatment;
[0042] (3) subjecting the surface of the material obtained in step (2) to magnetron sputtering of a metal target at a power of 50-100 W to obtain the sputtered carbon-based auxiliary filler;
[0043] The preparation method of the modified flaky silver-coated copper powder comprises the following steps:
[0044] (1) dispersing flaky silver-coated copper powder in anhydrous ethanol to prepare flaky silver-coated copper slurry;
[0045] (2) pouring the flaky silver-coated copper slurry into the modified solution, stirring for 20 minutes, standing, centrifuging, and drying to obtain the modified flaky silver-coated copper powder, wherein the modified solution is anhydrous ethanol.
[0046] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0047] Example 1: A modified and enhanced conductive adhesive, comprising the following raw materials: bisphenol A epoxy resin E-51: 19.2 g, methyl hexahydrophthalic anhydride: 11.8 g, modified flaky silver-coated copper powder: 67.3 g, silane coupling agent KH550: 1 g, cobalt (II) acetylacetonate: 0.4 g, carbon-based auxiliary filler (sputtering silver target): 0.3 g;
[0048] The preparation method comprises the following steps:
[0049] (1) Epoxy resin E51 was placed in a vacuum drying oven at a constant temperature of 60°C for 1 hour to improve the rheological properties of the epoxy resin;
[0050] (2) grinding cobalt (II) acetylacetonate to increase the fineness, then adding cobalt (II) acetylacetonate to epoxy resin E51 and stirring thoroughly, heating the vacuum drying oven to 60-100° C., placing the substrate in the oven, and maintaining the vacuum temperature for 30-60 min;
[0051] (3) adding KH550 and methyl hexahydrophthalic anhydride, stirring slowly, and ultrasonicating at 25-30° C. for 10-20 min until the stratification phenomenon disappears, thereby obtaining a modified matrix;
[0052] (4) fully shaking and mixing the carbon-based auxiliary filler obtained by sputtering the Ag target and the modified flaky silver-coated copper powder to obtain a mixed filler;
[0053] The preparation method of the carbon-based auxiliary filler comprises the following steps:
[0054] ① Disperse carbon black in an aqueous solution of sodium dodecyl sulfate and disperse by ultrasonic for 30-60 minutes;
[0055] ② Filter and vacuum dry the solution after the ultrasound treatment;
[0056] ③ The surface of the material obtained in ② is subjected to magnetron sputtering of an Ag target at a power of 80 W to obtain the carbon-based auxiliary filler;
[0057] (5) Adding the mixed filler into the modified matrix in batches and slowly stirring until uniformly mixed, the modified enhanced conductive adhesive can be obtained.
[0058] The conductive adhesive can be cured in an oven at 150°C.
[0059] Example 2: A modified and enhanced conductive adhesive, comprising the following raw materials: bisphenol A epoxy resin E-51: 19.2 g, methyl hexahydrophthalic anhydride: 11.8 g, modified flaky silver-coated copper powder: 67.3 g, silane coupling agent KH550: 1 g, cobalt (II) acetylacetonate: 0.4 g, carbon-based auxiliary filler (sputtering copper target): 0.3 g;
[0060] The preparation method comprises the following steps:
[0061] (1) Epoxy resin E51 was placed in a vacuum drying oven at a constant temperature of 60°C for 1 hour to improve the rheological properties of the epoxy resin;
[0062] (2) grinding cobalt (II) acetylacetonate to increase the fineness, then adding cobalt (II) acetylacetonate to epoxy resin E51 and stirring thoroughly, heating the vacuum drying oven to 60-100° C., placing the substrate in the oven, and maintaining the vacuum temperature for 30-60 min;
[0063] (3) adding KH550 and methyl hexahydrophthalic anhydride, stirring slowly, and ultrasonicating at 25-30° C. for 10-20 min until the stratification phenomenon disappears, thereby obtaining a modified matrix;
[0064] (4) fully shaking and mixing the carbon-based auxiliary filler obtained by sputtering the Cu target and the modified flaky silver-coated copper powder to obtain a mixed filler;
[0065] The preparation method of the carbon-based auxiliary filler comprises the following steps:
[0066] ① Disperse carbon black in an aqueous solution of sodium dodecyl sulfate and disperse by ultrasonic for 30-60 minutes;
[0067] ② Filter and vacuum dry the solution after the ultrasound treatment;
[0068] ③ The surface of the material obtained in ② is subjected to magnetron sputtering of a Cu target at a power of 80 W to obtain the carbon-based auxiliary filler;
[0069] (5) Adding the mixed filler into the modified matrix in batches and slowly stirring the mixture to obtain the modified enhanced conductive adhesive.
[0070] The conductive adhesive can be cured in an oven at 150°C.
[0071] Example 3: A modified and enhanced conductive adhesive, comprising the following raw materials: bisphenol A epoxy resin E-51: 19.2 g, methyl hexahydrophthalic anhydride: 11.8 g, modified flaky silver-coated copper powder: 67.3 g, silane coupling agent KH550: 1 g, cobalt (II) acetylacetonate: 0.4 g, carbon-based auxiliary filler (sputtering nickel target): 0.3 g;
[0072] The preparation method comprises the following steps:
[0073] (1) Epoxy resin E51 was placed in a vacuum drying oven at a constant temperature of 60°C for 1 hour to improve the rheological properties of the epoxy resin;
[0074] (2) grinding cobalt (II) acetylacetonate to increase the fineness, then adding cobalt (II) acetylacetonate to epoxy resin E51 and stirring thoroughly, heating the vacuum drying oven to 60-100° C., placing the substrate in the oven, and maintaining the vacuum temperature for 30-60 min;
[0075] (3) adding KH550 and methyl hexahydrophthalic anhydride, stirring slowly, and ultrasonicating at 25-30° C. for 10-20 min until the stratification phenomenon disappears, thereby obtaining a modified matrix;
[0076] (4) fully shaking and mixing the carbon-based auxiliary filler obtained by sputtering the Ni target and the modified flaky silver-coated copper powder to obtain a mixed filler;
[0077] The method for preparing the sputtered carbon-based auxiliary filler comprises the following steps:
[0078] ① Disperse carbon black in an aqueous solution of sodium dodecyl sulfate and disperse by ultrasonic for 30-60 minutes;
[0079] ② Filter and vacuum dry the solution after the ultrasound treatment;
[0080] ③ The surface of the material obtained in ② is subjected to magnetron sputtering of Ni target at a power of 80W to obtain the carbon-based auxiliary filler;
[0081] (5) Adding the mixed filler into the modified matrix in batches and slowly stirring the mixture to obtain the modified enhanced conductive adhesive.
[0082] The conductive adhesive can be cured in an oven at 150°C.
[0083] The only difference between Example 4 and Example 1 is that the power of sputtering the silver target with the carbon-based auxiliary filler is 60W.
[0084] Example 5 is different from Example 1 only in that the power of sputtering the silver target with the carbon-based auxiliary filler is 100W.
[0085] The only difference between Example 6 and Example 2 is that the power of sputtering the copper target with the carbon-based auxiliary filler is 60W.
[0086] The only difference between Example 7 and Example 2 is that the power of sputtering the copper target with the carbon-based auxiliary filler is 100W.
[0087] The only difference between Example 8 and Example 3 is that the power of sputtering the nickel target with the carbon-based auxiliary filler is 60W.
[0088] The only difference between Example 9 and Example 3 is that the power of sputtering the nickel target with the carbon-based auxiliary filler is 100W.
[0089] Comparative Example 1: A conductive adhesive comprising the following raw materials: bisphenol A epoxy resin E51: 19.2 g, methyl hexahydrophthalic anhydride: 11.8 g, modified flaky silver-coated copper powder: 67.3 g, silane coupling agent KH550: 1 g, cobalt (II) acetylacetonate: 0.4 g, carbon-based auxiliary filler (sputtering zinc target): 0.3 g;
[0090] The preparation method comprises the following steps:
[0091] (1) Epoxy resin E51 was placed in a vacuum drying oven at a constant temperature of 60°C for 1 hour to improve the rheological properties of the epoxy resin;
[0092] (2) grinding cobalt (II) acetylacetonate to increase the fineness, then adding cobalt (II) acetylacetonate to epoxy resin E51 and stirring thoroughly, heating the vacuum drying oven to 60-100° C., placing the substrate in the oven, and maintaining the vacuum temperature for 30-60 min;
[0093] (3) adding KH550 and methyl hexahydrophthalic anhydride, stirring slowly, and ultrasonicating at 25-30° C. for 10-20 min until the stratification phenomenon disappears, thereby obtaining a modified matrix;
[0094] (4) fully shaking and mixing the carbon-based auxiliary filler obtained by sputtering the Zn target and the modified flaky silver-coated copper powder to obtain a mixed filler;
[0095] The preparation method of the carbon-based auxiliary filler comprises the following steps:
[0096] ① Disperse carbon black in an aqueous solution of sodium dodecyl sulfate and disperse by ultrasonic for 30-60 minutes;
[0097] ② Filter and vacuum dry the solution after the ultrasound treatment;
[0098] ③ Magnetron sputtering of Zn target material on the surface of the material obtained in ② with a power of 80W to obtain the carbon-based auxiliary filler;
[0099] (5) Adding the mixed filler into the modified matrix in batches and slowly stirring the mixture to obtain the conductive adhesive.
[0100] The conductive adhesive can be cured in an oven at 150°C.
[0101] Comparative Example 2: A conductive adhesive comprising the following raw materials: bisphenol A epoxy resin E51: 19.2 g, methyl hexahydrophthalic anhydride: 11.8 g, modified flaky silver-coated copper powder: 67.3 g, silane coupling agent KH550: 1 g, cobalt (II) acetylacetonate: 0.4 g, carbon-based auxiliary filler (sputtering aluminum target): 0.3 g;
[0102] The preparation method comprises the following steps:
[0103] (1) Epoxy resin E51 was placed in a vacuum drying oven at a constant temperature of 60°C for 1 hour to improve the rheological properties of the epoxy resin;
[0104] (2) grinding cobalt (II) acetylacetonate to increase the fineness, then adding cobalt (II) acetylacetonate to epoxy resin E51 and stirring thoroughly, heating the vacuum drying oven to 60-100° C., placing the substrate in the oven, and maintaining the vacuum temperature for 30-60 min;
[0105] (3) adding KH550 and methyl hexahydrophthalic anhydride, stirring slowly, and ultrasonicating at 25-30° C. for 10-20 min until the stratification phenomenon disappears, thereby obtaining a modified matrix;
[0106] (4) fully shaking and mixing the carbon-based auxiliary filler obtained by sputtering the Al target and the modified flaky silver-coated copper powder to obtain a mixed filler;
[0107] The preparation method of the carbon-based auxiliary filler comprises the following steps:
[0108] ① Disperse carbon black in an aqueous solution of sodium dodecyl sulfate and disperse by ultrasonic for 30-60 minutes;
[0109] ② Filter and vacuum dry the solution after the ultrasound treatment;
[0110] ③ The surface of the material obtained in ② is subjected to magnetron sputtering of Al target material at a power of 80W to obtain the carbon-based auxiliary filler;
[0111] (5) Adding the mixed filler into the modified matrix in batches and slowly stirring the mixture to obtain the conductive adhesive.
[0112] The conductive adhesive can be cured in an oven at 150°C.
[0113] Comparative Example 3 is different from Comparative Example 1 only in that the power of sputtering the zinc target with the carbon-based auxiliary filler is 60W.
[0114] Comparative Example 4 is different from Comparative Example 1 only in that the power of sputtering the zinc target with the carbon-based auxiliary filler is 100W.
[0115] Comparative Example 5 is different from Comparative Example 2 only in that the power of sputtering the aluminum target with the carbon-based auxiliary filler is 60W.
[0116] Comparative Example 6 is different from Comparative Example 2 only in that the power of sputtering the aluminum target with the carbon-based auxiliary filler is 100W.
[0117] Comparative Example 7: A conductive adhesive comprising the following raw materials: 19.2 g of bisphenol A epoxy resin E-51, 11.8 g of methyl hexahydrophthalic anhydride, 67.6 g of modified flaky silver-coated copper powder, 1 g of silane coupling agent KH550, and 0.4 g of cobalt (II) acetylacetonate;
[0118] The preparation method comprises the following steps:
[0119] (1) Epoxy resin E51 was placed in a vacuum drying oven at a constant temperature of 60°C for 1 hour to improve the rheological properties of the epoxy resin;
[0120] (2) grinding cobalt (II) acetylacetonate to increase the fineness, then adding cobalt (II) acetylacetonate to epoxy resin E51 and stirring thoroughly, heating the vacuum drying oven to 60-100° C., placing the substrate in the oven, and maintaining the vacuum temperature for 30-60 min;
[0121] (3) adding KH550 and methyl hexahydrophthalic anhydride, stirring slowly, and ultrasonicating at 25-30° C. for 10-20 min until the stratification phenomenon disappears, thereby obtaining a modified matrix;
[0122] (4) Adding the modified flaky silver-coated copper powder into the modified matrix in batches and slowly stirring the mixture to obtain the conductive adhesive.
[0123] The conductive adhesive can be cured in an oven at 150°C.
[0124] Comparative Example 8: A conductive adhesive comprising the following raw materials: bisphenol A epoxy resin E51: 19.2 g, methyl hexahydrophthalic anhydride: 11.8 g, modified flaky silver-coated copper powder: 67.3 g, silane coupling agent KH550: 1 g, cobalt (II) acetylacetonate: 0.4 g, and carbon-based auxiliary filler (carbon black): 0.3 g;
[0125] The preparation method comprises the following steps:
[0126] (1) Epoxy resin E51 was placed in a vacuum drying oven at a constant temperature of 60°C for 1 hour to improve the rheological properties of the epoxy resin;
[0127] (2) grinding cobalt (II) acetylacetonate to increase the fineness, then adding cobalt (II) acetylacetonate to epoxy resin E51 and stirring thoroughly, heating the vacuum drying oven to 60-100° C., placing the substrate in the oven, and maintaining the vacuum temperature for 30-60 min;
[0128] (3) adding KH550 and methyl hexahydrophthalic anhydride, stirring slowly, and ultrasonicating at 25-30° C. for 10-20 min until the stratification phenomenon disappears, thereby obtaining a modified matrix;
[0129] (4) fully shaking and mixing the carbon-based auxiliary filler and the modified flaky silver-coated copper powder to obtain a mixed filler;
[0130] The preparation method of the carbon-based auxiliary filler comprises the following steps:
[0131] ① Disperse carbon black in an aqueous solution of sodium dodecyl sulfate and disperse by ultrasonic for 30-60 minutes;
[0132] ② Filter and vacuum dry the solution after the ultrasound treatment;
[0133] (5) Add the mixed filler into the matrix in batches and slowly stir until uniformly mixed, thereby obtaining the conductive adhesive.
[0134] The conductive adhesive can be cured in an oven at 150°C.
[0135] Comparative Example 9: A conductive adhesive comprising the following raw materials: bisphenol A epoxy resin E51: 19.2 g, methyl hexahydrophthalic anhydride: 11.8 g, modified flaky silver-coated copper powder: 67.3 g, silane coupling agent KH550: 1 g, cobalt (II) acetylacetonate: 0.4 g, carbon-based auxiliary filler (carbon nanotube): 0.3 g;
[0136] The preparation method comprises the following steps:
[0137] (1) Epoxy resin E51 was placed in a vacuum drying oven at a constant temperature of 60°C for 1 hour to improve the rheological properties of the epoxy resin;
[0138] (2) Grinding cobalt (II) acetylacetonate to increase the fineness, then adding cobalt (II) acetylacetonate salt to epoxy resin E51 and stirring thoroughly, heating the vacuum drying oven to 60-100° C., placing the substrate in the oven, and maintaining the vacuum temperature for 30-60 min;
[0139] (3) adding KH550 and methyl hexahydrophthalic anhydride, stirring slowly, and ultrasonicating at 25-30° C. for 10-20 min until the stratification phenomenon disappears, thereby obtaining a modified matrix;
[0140] (4) fully shaking and mixing the carbon-based auxiliary filler and the modified flaky silver-coated copper powder to obtain a mixed filler;
[0141] The preparation method of the carbon-based auxiliary filler comprises the following steps:
[0142] ① Disperse the carbon nanotubes in an aqueous solution of sodium dodecyl sulfate and perform ultrasonic dispersion for 30-60 minutes;
[0143] ② Filter and vacuum dry the solution after the ultrasound treatment;
[0144] (5) Adding the mixed filler into the modified matrix in batches and slowly stirring the mixture to obtain the conductive adhesive.
[0145] The conductive adhesive can be cured in an oven at 150°C.
[0146] Comparative Example 10: A conductive adhesive comprising the following raw materials: bisphenol A epoxy resin E51: 19.2 g, methyl hexahydrophthalic anhydride: 11.8 g, modified flaky silver-coated copper powder: 67.3 g, silane coupling agent KH550: 1 g, cobalt (II) acetylacetonate: 0.4 g, and carbon-based auxiliary filler (carbon fiber): 0.3 g;
[0147] The preparation method comprises the following steps:
[0148] (1) Epoxy resin E51 was placed in a vacuum drying oven at a constant temperature of 60°C for 1 hour to improve the rheological properties of the epoxy resin;
[0149] (2) grinding cobalt (II) acetylacetonate to increase the fineness, then adding cobalt (II) acetylacetonate to epoxy resin E51 and stirring thoroughly, heating the vacuum drying oven to 60-100° C., placing the substrate in the oven, and maintaining the vacuum temperature for 30-60 min;
[0150] (3) adding KH550 and methyl hexahydrophthalic anhydride, stirring slowly, and ultrasonicating at 25-30° C. for 10-20 min until the stratification phenomenon disappears, thereby obtaining a modified matrix;
[0151] (4) fully shaking and mixing the carbon-based auxiliary filler and the modified flaky silver-coated copper powder to obtain a mixed filler;
[0152] The preparation method of the carbon-based auxiliary filler comprises the following steps:
[0153] ① Disperse the carbon fiber in an aqueous solution of sodium dodecyl sulfate and ultrasonically disperse for 30-60 minutes;
[0154] ② Filter and vacuum dry the solution after the ultrasound treatment;
[0155] (5) Adding the mixed filler into the modified matrix in batches and slowly stirring the mixture to obtain the conductive adhesive.
[0156] The conductive adhesive can be cured in an oven at 150°C.
[0157] Performance Testing:
[0158] Different carbon materials: carbon black, carbon nanotubes and carbon fibers were added to an aqueous solution of sodium dodecyl sulfate and dispersed to obtain the average particle size results as shown in the figure. Figure 1 As shown, the XRD comparison before and after dispersion is Figure 2 As shown, the electron microscope images before and after dispersion are as follows Figure 3 As shown;
[0159] The surface electron microscope images and corresponding EDS elemental spectra of Ag, Cu and Ni targets sputtered on carbon black as substrate are shown in the figure. Figure 4 As shown;
[0160] According to the ASTM D257-2007 test standard, the volume resistivity of the samples obtained from the above embodiments 1-9 and comparative examples 1-10 was tested; the thermal conductivity of the samples obtained from the above embodiments 1-9 and comparative examples 1-10 was tested; according to the national standard GB / T7124-2008 test standard, the shear strength of the samples obtained from the above embodiments 1-9 and comparative examples 1-10 was tested, and the results are shown in Table 1:
[0161] Table 1
[0162]
[0163]
[0164] according to Figure 1 , 2 , 3 and Table 1, it can be seen that carbon materials with different substrates have different effects on electrical conductivity, thermal conductivity and shear force. The particle sizes of carbon materials after ultrasonic treatment are different. The smaller the particle size, the better the comprehensive performance. It can be seen from the table that carbon black, as a carbon-based material, has the best comprehensive performance. Compared with materials without carbon addition, the electrical conductivity and thermal conductivity are qualitatively improved. Sputtering metal nanoparticles with carbon black as the substrate can form a dense metal conductive network, greatly improve the electrical conductivity and thermal conductivity, and the shear strength does not change much, which can meet the industrial requirements in the field of electronic packaging. By comparing different metal targets, it is found that the improvement of the comprehensive performance of the conductive adhesive brought by the silver target is greater than that of copper, nickel, zinc and aluminum targets. The sputtering rate of the metal target is moderate and can be evenly covered on the surface of the carbon black particles. By comparing different sputtering powers, if the sputtering rate is too fast, the metal particles may be too large or unevenly distributed, which will reduce the electrical conductivity and thermal conductivity of the conductive adhesive. Therefore, it is necessary to choose a suitable sputtering power.
[0165] To sum up, the epoxy resin conductive adhesive doped with sputtered carbon-based auxiliary materials prepared in the embodiment of the present invention can make the conductive adhesive doped with a small amount of nano-metal particles have higher conductivity, thermal conductivity and shear strength, and also greatly reduce the production cost and improve the market competitiveness of the product. The product can be widely used in semiconductor packaging, LED packaging, solar cells, electronic display screens and other fields.
[0166] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A modified and enhanced conductive adhesive, characterized in that: The invention comprises the following raw materials in weight percentage: 18-25% of bisphenol A epoxy resin, 60-75% of modified flaky silver-coated copper powder, 0.2-0.5% of sputtered carbon-based auxiliary filler, 0.3-0.5% of acetylacetone metal salt, 1.1-1.6% of coupling agent, and the balance of curing agent.
2. The modified and enhanced conductive adhesive according to claim 1, characterized in that: The bisphenol A epoxy resin is bisphenol A epoxy resin E-51 or a mixture of bisphenol A epoxy resin E-51 and bisphenol A epoxy resin E-42, and the weight ratio of bisphenol A epoxy resin E-51 to bisphenol A epoxy resin E-42 in the mixture is 18-20:1-3.
3. The modified and enhanced conductive adhesive according to claim 1, characterized in that: The coupling agent is one of silane coupling agents KH-550 and KH-570 or a mixture of the two, and the weight ratio of KH-550 to KH-570 is 17-19:1-2.
4. The modified and enhanced conductive adhesive according to claim 1, characterized in that: The acetylacetonate metal salt is one of cobalt (II) acetylacetonate, cobalt (III) acetylacetonate, and chromium acetylacetonate, or a mixture of the three. The weight ratio of cobalt (II) acetylacetonate, cobalt (III) acetylacetonate, and chromium acetylacetonate is 1:0.1-0.4:0.1-0.
4.
5. The modified and enhanced conductive adhesive according to claim 1, characterized in that: The curing agent is methylhexahydrophthalic anhydride or a mixture of methylhexahydrophthalic anhydride and methyltetrahydrophthalic anhydride, and the weight ratio of methylhexahydrophthalic anhydride to methyltetrahydrophthalic anhydride in the mixture is 17-19:1-3.
6. The modified and enhanced conductive adhesive according to claim 1, characterized in that: The modified flaky silver-coated copper powder has a particle size of 5-10 μm and a thickness of 250-500 nm. The preparation method thereof comprises the following steps: Dispersing flaky silver-coated copper powder in anhydrous ethanol to prepare flaky silver-coated copper slurry; The modified flaky silver-coated copper powder is obtained by pouring the flaky silver-coated copper slurry into the modified solution, stirring, standing, centrifuging and drying. The modified solution is anhydrous ethanol or a mixed solution of anhydrous ethanol and ethylene glycol. The weight ratio of anhydrous ethanol to ethylene glycol in the mixed solution is 1-4:1-5.
7. The modified and enhanced conductive adhesive according to claim 1, characterized in that: The preparation method of the sputtered carbon-based auxiliary filler comprises the following steps: Dispersing the carbon material in an aqueous solution of a surfactant and performing ultrasonic dispersion; After the ultrasonic dispersion is completed, the mixture is filtered and dried, and a metal target is magnetron sputtered on the surface to obtain the sputtered carbon-based auxiliary filler.
8. The modified and enhanced conductive adhesive according to claim 7, characterized in that: The carbon material is one of carbon black, carbon fiber, and carbon nanotubes, or a mixture of the three, and the weight ratio of carbon black, carbon fiber, and carbon nanotubes is 1-3:1-2:1-3; The surfactant is one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate or a mixture of the two; The metal target material for sputtering is one or a mixture of silver target, copper target, and nickel target. The sputtering power of the silver target, copper target, and nickel target is 50-100W.
9. A method for preparing the modified and enhanced conductive adhesive according to any one of claims 1 to 8, characterized in that: The following steps are involved: The bisphenol A epoxy resin is heated at a constant temperature; Grinding the acetylacetone metal salt, adding the acetylacetone metal salt to the bisphenol A epoxy resin, and stirring thoroughly to obtain a matrix; Adding a coupling agent and a curing agent into the matrix, performing ultrasonic treatment, and waiting for the stratification phenomenon to disappear, thereby obtaining a modified matrix; The sputtered carbon-based auxiliary filler and the modified flaky silver-coated copper powder are fully shaken and mixed to obtain a mixed filler; The mixed filler is added into the modified matrix in batches and slowly stirred to obtain the modified enhanced conductive adhesive.
10. Use of the modified and enhanced conductive adhesive according to any one of claims 1 to 8 in preparing semiconductor packaging materials.
Citation Information
Patent Citations
Conductive adhesive for over-temperature overcurrent protective element and production method thereof
CN103436197A
Magnetron sputtering target material assembly and preparation method thereof
CN111172505A
Nano electric conduction and heat conduction adhesive and application thereof
CN112063345A
Conductive adhesive as well as preparation method and application thereof
CN116103000A
Methods for preparing a carbon nanotube conductive ball and a carbon nanotube ball conductive adhesive
US20170260426A1
